What have I learned from Marx and what remain valid? - Przeworski, Adam (2021)
Should one read Marx today? Which of his theories survive the test of time and which should be abandoned? This article reviews four of Marx’s topics: the quest for material abundance, the compatibility of capitalism and democracy, the role of the state, and the theory of the dynamics of capitalism.